Study on stability control of stope structural in short-wall cemented backfill mining for recovery of room-and-pillar residual coal - Yun ZHANG; Long ZHANG; Xingping LAI; Shenggen CAO; Yanbin YANG; Yongzi LIU; Rui ZHAN; Licheng BAI; Hao YE (Meitan kexue jishu)
The stagnation of residual coal pillars from room-and-pillar mining and the discharge of mine solid waste have severely constrained the green and low-carbon transformation of China’s coal industry. To address these challenges, the Bandingliang Coal Mine in northern Shaanxi as the engineering case study, a novel "time-sequence coordinated pillar replacement" short-wall cemented backfill mining technique was proposed. First, the safe stress for the recovery of residual coal pillars from room-and-pillar mining was calculated based on the limit strength theory. Secondly, numerical simulation was used to study the instability characteristics of the natural collapse method for managing the recovery of residual coal pillars and the impact of roof failure on the stability of the mining area. A mechanical model for the short-wall cemented backfill stope was established, and the critical strength of the backfill material was solved to ensure that the direct roof would not fail. Finally, mechanical tests were performed to analyze the mechanical properties, failure characteristics, and microstructural features of the cemented backfill, and a complete design method for short-wall cemented backfill mining was proposed based on the actual engineering. The results indicated that the safe stress value for the residual coal pillar in Bandingliang Coal Mine was 11.78 MPa, which met the conditions for safe recovery. Based on the stress, plastic zone distribution characteristics, and roof failure analysis during the recovery of residual coal pillars using the natural caving method, It was discovered that the recycling process may trigger a “domino” chain reaction, accompanied by large-scale roof failure. Furthermore, the short-wall cemented backfill mining technique was proposed to replace the residual coal pillars, and the critical backfill strength required to prevent roof collapse was calculated to be 8.97 MPa. Based on this, the optimal mix ratio of coal gangue∶fly ash∶cement∶water in the backfill material was determined as 3∶3∶1∶1. This mix ratio provided superior gangue particle grading, and the hydration products densely filled the gaps between aggregates, effectively reducing porosity and significantly improving mechanical performance, thus meeting the safe recovery requirements for coal pillars in Bandingliang Coal Mine. Feasibility designs for the short-wall cemented backfill mining production system and key parameters in the experimental recovery area were proposed, along with control measures to ensure the effectiveness of the backfill. The research results provided a replicable engineering paradigm for the “resource recovery-ecological protection-solid waste utilization” integrated green and low-carbon transformation and development of the coal industry in China.